Survey strategies to quantify and optimize detecting probability of a CO2 seep in a varying marine environment. (September 2016) - Hvidevold, Hilde Kristine; Alendal, Guttorm; Johannessen, Truls; Ali, Alfatih
Abstract: Designing a marine monitoring program that detects CO2 leaks from subsea geological storage projects is challenging. The high variability of the environment may camouflage the anticipated anisotropic signal from a leak and there are a number of leak scenarios. Marine operations are also costly constraining the availability of measurements. A method based on heterogeneous leak scenarios and anisotropic predictions of chemical footprint under varying current conditions is presented. Through a cost function optimal placement of sensors can be given both for fixed installations and series of measurements during surveys. Ten fixed installations with an optimal layout is better than twenty placed successively at the locations with highest leakage probability. Hence, optimal localizations of installations offers cost reduction without compromising precision of a monitoring program, e.g. quantifying and reduce probabilities of false alarm under control. An optimal cruise plan for surveys, minimizing transit time and operational costs, can be achieved. Highlights: Seafloor monitoring design to detect leaks from geological CO2 storage. Based on site characterization, local environmental statistics and a detection threshold. Quantifies the probability of detecting a leak and finds the optimal layout. Likelihood of adverse measurements being false alarm is quantified. Can be extended to include other constraints, e.g. cost or vulnerable areas.